Executive Extraversion: Career and Firm Outcomes - Green, T. Clifton; Jame, Russell; Lock, Brandon (The Accounting Review, 2019)
ABSTRACT Psychology research identifies extraversion as the personality trait most closely associated with leadership emergence. We examine executive extraversion, as measured by speech patterns during conference calls, and find extraverts experience significant career benefits. Controlling for executive and firm characteristics, including firm fixed effects, we find that extraverted CEOs and CFOs earn 6–9 percent higher salaries. Moreover, extraverted CEOs are less likely to experience job turnover, have longer tenures, serve on more outside boards, and hold directorships at larger firms, and extraverted CFOs are more likely to be promoted to CEO. Executive extraversion is also linked with firm outcomes. Analyzing a sample of manager transitions, we find that increases in CEO extraversion are associated with improvements in investor recognition and sales growth. Further, extraverted CEOs are associated with higher acquisition announcement returns. Our findings highlight the role of personality traits in explaining executive career and firm outcomes. JEL Classifications: G14.